1988
DOI: 10.3354/meps045217
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of particle retention and filtration rate in 6 species of Northeast American bivalves

Abstract: ABSTRACT. Particle retention efficiency in 6 species of suspension-feeding Northeast American bivalves was determined by simultaneous measurement of clearance of different sized particles.Geukensia dernissa, Spisula solidissirna, Brachidontes exustus, and Mercenaria rnercenana, which all possess large laterofrontal cirri, completely retained particles above 4 pm. Below this the retention efficiency gradually decreased to between 35 and 70 % for 2 kim particles. Crassostrea virginica, which has small laterofron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
231
1
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(247 citation statements)
references
References 15 publications
(19 reference statements)
11
231
1
4
Order By: Relevance
“…A recent review by Cranford et al (2011) suggested that the constant b could be universally written as 0.58 for filter-feeding bivalves. While species-specific estimates for C. virginica are rare, they have ranged from 0.59 (Pruder et al 1976 cited in Epifanio andEwart 1977) to 0.73±0.22 (Riisgaard 1988). Using the Levenberg-Marquardt nonlinear least squares method (Press et al 2007) in Mathematica version 7, we fitted Eq.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review by Cranford et al (2011) suggested that the constant b could be universally written as 0.58 for filter-feeding bivalves. While species-specific estimates for C. virginica are rare, they have ranged from 0.59 (Pruder et al 1976 cited in Epifanio andEwart 1977) to 0.73±0.22 (Riisgaard 1988). Using the Levenberg-Marquardt nonlinear least squares method (Press et al 2007) in Mathematica version 7, we fitted Eq.…”
Section: Methodsmentioning
confidence: 99%
“…The physiology of oyster feeding and filtration is well studied, and filtration rate is known from laboratory studies to be influenced by a variety of environmental factors such as temperature, flow rate, salinity, seston concentration, and particle size, as well as oyster size (Loosanoff 1958;Walne 1972;Shumway et al 1985;Riisgaard 1988). Although it is recognized that conditions in situ may significantly affect filtration rate (Doering and Oviatt 1986;Powell et al 1992), few studies have sought to quantify rates under field conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies (for review, see Hawkins & Bayne 1992) have shown that Mytilus edulis, like most suspensionfeeders, has only a limited capacity to ingest small, natural-sized ( c 1 pm) bacteria. As an exception, however, Geukensia demissa has been reported capable of filtering natural-slzed bacteria with efficiencies 18 to 30% of those of larger dietary particles (Wright et al 1982, Riisgdrd 1988). Our ingestion results are consistent with these findings.…”
Section: Diet Culturesmentioning
confidence: 99%
“…Filtration rates (FR) can vary widely among bivalve species (Moehlenberg and Riisgaard 1979;Riisgaard 1988) and have not previously been determined for O. lurida. Here, we present the results of the first laboratory-based measurements of FR by O. lurida and propose a model of FR as it varies with oyster size and temperature.…”
Section: Introductionmentioning
confidence: 99%